215 WHAT IMPACT CAN 'EMERGENCY DEPARTMENT IN THE HOME' (EDITH) HAVE ON THE OLDER ADULT POPULATION PRESENTING WITH FALLS?. (18th November 2021) - Delaney, A; Doyle, C; Sweeney, A; Davis, A; McNally, S; McNamara, R; Mooney, R
Abstract: Background: EDITH is a frailty response service providing medical and occupational therapy input to older adults living within the catchment area of a level 4 acute hospital. EDITH aims to reduce avoidable Emergency Department (ED) attendances and utilise alternative care pathways. Falls are common among older people and are often associated with poorer outcomes. Traditionally, older patients who have had a fall and contact emergency services for assistance are transferred to the ED and this can be associated with elevated risks. Additionally, older patients who have had a fall and are discharged on scene by the emergency services are at greater risk of recurring falls in the absence of immediate onward referral to community falls prevention services (Nowak and Hubbard 2009). Methods: Paper count method data collection was completed. Inclusion criteria included referrals from the National Ambulance Service within the last 6 months. Results: 75 patients met the inclusion criteria; 34 males, 41 females with an average age of 82. 11 patients were conveyed to hospital, giving a conveyance rate of 14.6%, the average conveyance rate for the EDITH service is 7.2%. 3 patients were conveyed to ED, while 8 patients were conveyed to the Medical Assessment Unit (MAU) in the local level 3 hospital. This resulted in 72% of patients that required hospital conveyance being streamed to the MAU; traditionally 100% of these patients would have presented to ED. Overall, 85.4% of patients seen remained at home. Conclusion: EDITH are providing targeted medical and occupational therapy assessment(s) for older adults in their homes with successful outcomes. Implementation of alternative care pathways, reduction in avoidable ED attendances and prolonged independence in the home for this patient profile are some of the favourable findings. Reference: 1. Nowak A, Hubbard RE. (2009) Falls and frailty: lessons from complex systems. Journal of the Royal Society of Medicine . 102(3):98–102.